Succinate Activates EMT in Intestinal Epithelial Cells through SUCNR1: A Novel Protagonist in Fistula Development - Ortiz-Masiá, Dolores; Gisbert-Ferrándiz, Laura; Bauset, Cristina; Coll, Sandra; Mamie, Céline; Scharl, Michael; Esplugues, Juan V.; Alós, Rafael; Navarro, Francisco; Cosín-Roger, Jesús; Barrachina, María D.; Calatayud, Sara (Cells (Basel, Switzerland), 2020)
The pathogenesis of Crohn’s disease-associated fibrostenosis and fistulas imply the epithelial-to-mesenchymal transition (EMT) process. As succinate and its receptor (SUCNR1) are involved in intestinal inflammation and fibrosis, we investigated their relevance in EMT and Crohn’s disease (CD) fistulas. Succinate levels and SUCNR1-expression were analyzed in intestinal resections from non-Inflammatory Bowel Disease (non-IBD) subjects and CD patients with stenosing-B2 or penetrating-B3 complications and in a murine heterotopic-transplant model of intestinal fibrosis. EMT, as increased expression of Snail1, Snail2 and vimentin and reduction in E-cadherin, was analyzed in tissues and succinate-treated HT29 cells. The role played by SUCNR1 was studied by silencing its gene. Succinate levels and SUCNR1 expression are increased in B3-CD patients and correlate with EMT markers. SUCNR1 is detected in transitional cells lining the fistula tract and in surrounding mesenchymal cells. Grafts from wild type (WT) mice present increased succinate levels, SUCNR1 up-regulation and EMT activation, effects not observed in SUCNR1−/− tissues. SUCNR1 activation induces the expression of Wnt ligands, activates WNT signaling and induces a WNT-mediated EMT in HT29 cells. In conclusion, succinate and its receptor are up-regulated around CD-fistulas and activate Wnt signaling and EMT in intestinal epithelial cells. These results point to SUCNR1 as a novel pharmacological target for fistula prevention.